The impact of advanced patient age on mortality after allogeneic hematopoietic cell transplantation for non-hodgkin lymphoma: a retrospective study by the European Society for Blood and Marrow Transplantation lymphoma working party - Kyriakou, Charalampia; Dreger, Peter (Biology of blood and marrow transplantation, 2019)
More than 60% of patients with non-Hodgkin lymphoma (NHL) are age >60 years at presentation. The purpose of this study was to compare the potential risks and benefits of allogeneic hematopoietic cell transplantation (alloHCT) in elderly patients with NHL with younger patients in a large sample, also taking into account comorbidity information. All patients age ≥18 years who had undergone alloHCT from a matched sibling or unrelated donor for NHL between 2003 and 2013 and were registered with the European Society for Blood and Marrow Transplantation were eligible for the study. The primary study endpoint was 1-year nonrelapse mortality (NRM). A total of 3919 patients were eligible and were categorized by age: young (Y), 18 to 50 y (n=1772); middle age (MA), 51 to 65 y (n=1967); or old (O), 66 to 77 y (n=180). Follicular lymphoma was present in 37% of the patients; diffuse large B cell lymphoma, in 30%; mantle cell lymphoma, in 21%, and peripheral T cell lymphoma, in 11%. At the time of alloHCT, 85% of the patients were chemosensitive and 15% were chemorefractory. With a median follow-up of 4.5 years in survivors, NRM at 1 year was 13% for the Y group. 20% for the MA group, and 33% for the O group (P <.001), whereas relapse incidence and overall survival (OS) at 3 years in the 3 groups were 30%, 31%, and 28% (P=.355) and 60%, 54%, and 38% (P <.001), respectively. Multivariable adjustment for confounders, including sex, NHL subset, time from diagnosis, chemosensitivity, donor, and conditioning, confirmed older age as a significant predictor for NRM and OS, but not for relapse risk. Although comorbidity was a significant predictor of NRM in a subset analysis restricted to the 979 patients with comorbidity information available, age retained its significant impact on NRM. In conclusion, our data show that alloHCT in patients age >65 y provides similar NHL control as seen in younger patients but is associated with a higher NRM that is not fully explained by comorbidity. Thus, although alloHCT is feasible and effective in very old patients, the increased NRM risk must be taken into account when assessing the indication for alloHCT for NHL in this age group.
Available online 13 September 2018
Gesehen am 25.07.2019